Análise da aquisição de imóvel em planta: um estudo de caso para auxílio na tomada de decisões econômicas e viabilidade de investimento financeiro - BORGES JÚNIOR, William Machado (2018)
Brazil has experienced times of economic prosperity and real estate speculation. The Consequence of this experience is a great demand for residential property “in the architectural floor plan” or even for financial investment. Therefore, this study aims to simulate the purchase of a new apartment in the “in the architectural floor plan” located in Imperatriz-MA, in order to assist decision makings for various economic alternatives that affect who acquires or intends to acquire a property in the “in the architectural floor plan” through a sensitivity analysis of the factors involved in the cash flow such as the National Index of Construction, Period of Funding, interest rate of financing and attractiveness rate. Besides that, it unveils that the viability of acquiring the property in installments or in cash with a minimum discount necessary to purchase the property is worth. It will also analyze the financial viability of the property sale in the moment of the property keys delivery by the construction firm, explaining the financial benefits of the investment. For this purpose, cash flows of the apartment‟s payments to the construction firm were simulated during the construction of the apartment, and later to Caixa Economica Federal. The main conclusions of this study were: the sensitivity analysis indicated that the most impacting factors of the project are the minimum attractive rate and interest rate financing. To acquire the property in installments in fourteen simulated situations was more interesting, on the other hand to acquire the property in cash in a single simulated situation was more advantageous. The lower the current value, the higher the cash discount must be to make the option “pay in cash” be worthy. The viability analysis and the financial benefits of the investment indicated that the property sale is economically viable to the simulated situations shown on this study, after the delivery of the apartment keys with an appreciation of 40%. Through the rates of return that the investment will provide, it was possible to prove that all involved simulated situations cause a significant return. The study proved that the minimum rate of appreciation necessary to make the project be a good business is from 20.2%. Therefore, it was financially proved that, in fact, for this case study, the investment on the property in “the architectural floor plan” is worthy. Ergo, all the results indicate that there is economic viability of buying and selling apartments “in the architectural floor plan”.